Frequency diverse array beampattern synthesis method with low sidelobes by integrating mayfly algorithm and convex programming - Mengxuan Xiao; Xiaolang Shao; Taiyang Hu; Jinyu Zhang; Zelong Xiao (Electronics Letters, 2023)
Abstract The range‐angle coupling characteristics of traditional frequency diverse array (FDA) will deteriorate target localization performance. To address this problem, several decoupling methods for FDA have been developed in the past decade, mainly including deterministic methods and global optimization methods. However, most of these methods are based on frequency offset design and do not fully utilize other design degrees of freedom, such as excitation and element spacing, which limits obtained pattern performance. In this letter, a low‐sidelobe FDA pattern synthesis method is proposed by jointly optimizing frequency offset, array spacing and excitation. The entire optimization process is treated as two sub‐optimization problems, that is, a non‐convex sub‐problem involves frequency offset and array spacing, and a convex sub‐problem involves excitation. By integrating the mayfly algorithm and convex programming techniques, this synthesis problem can be effectively solved. Compared with the current state‐of‐the‐art counterparts, the proposed method takes full advantage of the FDA's design freedom and generates a doted beampattern with lower sidelobes.